Mendelian randomization suggests causal correlations between inflammatory cytokines and immune cells with mastitis - Chen, Jiaying; Su, Ben; Zhang, Xinyue; Gao, Chao; Ji, Yajie; Xue, Xiaohong (Frontiers in Immunology, 2024)
Previous studies have reported that immunoinflammatory responses have associations with mastitis. Here, we aimed to further figure out whether circulating inflammatory cytokines and immune cells causally impact mastitis liability.The two-sample Mendelian randomization made use of genetic variances of 91 inflammatory cytokines from a large publicly available genome-wide association study (GWAS) containing 14,824 participants, 731 immunophenotypes data from 3,757 individuals as exposures separately, and mastitis from a GWAS summary (1880 cases and 211699 controls of European ancestry) as outcome. The primary analysis applied the inverse-variance weighted (IVW) method to estimate causal influences, with MR-Egger, weighted median, weighted mode and simple mode as supplementary approaches. Heterogeneity and pleiotropy were evaluated by the Cochrane Q test, MR-Egger intercept test, and MR-PRESSO global test.The results indicated that CX3CL1 may be suggestively relevant to the risk of mastitis (odds ratio, OR = 1.434, 95% CI = 1.142~1.800, pP = 0.002). Moreover, three immunophenotypes were identified as having a potential causal link to mastitis (p < 0.05). Significantly, CD28-CD8dim %CD8dim (OR = 1.058, 95% CI = 1.024 ~ 1.093, pP = 0.0006) and CD45 on CD33br HLA DR+ (OR = 1.097, 95% CI = 1.039 ~ 1.157, pP = 0.0008) were found to induce mastitis possibly. Conversely, CD39+ secreting Treg AC (OR = 0.929, 95% CI = 0.884~ 0.978, pP = 0.005) pertained to protective factors of mastitis. Cochran's Q test and MR-Egger intercept test indicated no significant heterogeneity (p > 0.05) or pleiotropy (p > 0.05), supporting the robustness and reliability of our findings.